Effects of Momordica charantia (MC) Extract on Clinical Symptoms, Parasite Account, Thrombocytes, Total Bilirubin and Direct Bilirubin in Patients with Uncomplicated Plasmodium falciparum Malaria: A Case Report - Yudianto, Dian; Syamsudin Abdillah; Hesty Utami Ramadaniaty; Erni Juwita Nelwan (HM Publisher, 2024)
Clinical symptoms during the treatment of uncomplicated P. falciparum malaria have been reported in several studies. Parasite density in the blood is associated with clinical symptoms, platelet, and bilirubin count. A 52-year-old male, weighing 52 kg, was given one capsule containing 325 mg bitter melon (Momordica charantia) extract for 3 days of treatment. Patients were followed up for 28 days, days 1,2,3,4,7,14,21,28, and peripheral blood microscopic examination and clinical symptoms were carried out. Measurement of platelets, total bilirubin, direct bilirubin D0, D14 and D28. Naranjo Scale, adverse events measurements were taken on D7, no signs of severe malaria, no comorbidities, no history of malaria, blood pressure 110/80 mmHg, peripheral blood parasite examination on D0 found P. falciparum parasites of 31,714/µL, D0 platelet value of 94x10 /mm3, D0 total bilirubin value of 1.3 mg% and D0 direct bilirubin value of 0.6 mµ/mL. On D1 parasite count was 2,400/µL, D2 was 372/µL, D3, D4, D7, D14, D21, D28 no asexual parasites were found again. Clinical symptoms that arose on D0 were nausea, no appetite, sweating, chills, sleep disturbance, dizziness, headache, and weakness with a body temperature of 37°C. After D3 of bitter melon extract treatment, no clinical symptoms were found again. Naranjo scale score based on nurse and pharmacist agreement was 6 (probable) at D7 for the adverse events of nausea and vomiting. There were no reported adverse events such as nausea, vomiting, diarrhea, abdominal pain, cough, sleep disturbance, dizziness, headache and weakness on D2 treatment. Bitter melon extract is effective for uncomplicated malaria P. falciparum, reduces clinical symptoms, and is safe.